Advanced building materials selected, peer reviewed papers from the 2011 International conference on Civil Engineering, Architecture and Building Materials (CEABM2011), May 18-20, 2011, Haikou, China - Li, Guangfan (Trans Tech Publications, 2011)
Annotation This collection of papers, which was subjected to strict peer-review by 2 to 4 expert referees, aims to collect together the latest advances in, and applications of, traditional constructional materials, advanced constructional materials and green building materials. It cannot fail to suggest new ideas and strategies to be tried in this field.
Keywords: Technology -- Information services -- Congresses.; Engineering -- Bibliography -- Congresses.; elektronické knihy; electronic books